2023
DOI: 10.1002/ccd.30549
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sex on in‐hospital mortality and 90‐day readmissions in patients undergoing transcatheter mitral valve replacement (TMVR): Analysis from the nationwide readmission database

Abstract: Objectives: To evaluate sex differences in in-hospital mortality and 90-day readmission rates among patients undergoing transcatheter mitral valve replacement (TMVR) in the United States of America.Background: Women have higher rates of mortality and rehospitalization than men following many cardiac procedures. TMVR has grown as an alternative to mitral valve surgery for patients at high surgical risk. The rates of TMVR mortality and rehospitalization by sex are unknown. Methods:We analyzed the Nationwide Read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“… 7 , 31 There was a significant increase in the use of TMVR from 2016 to 2020 across all racial and ethnic groups and in both sexes. 32 Similarly, previous studies found an upward trend in other transcatheter valvular procedures in White and Black patients. 16 , 33 Elbadawi et al found that M‐TEER was increasingly performed in both White and Black patients at similar rates.…”
Section: Discussionmentioning
confidence: 67%
“… 7 , 31 There was a significant increase in the use of TMVR from 2016 to 2020 across all racial and ethnic groups and in both sexes. 32 Similarly, previous studies found an upward trend in other transcatheter valvular procedures in White and Black patients. 16 , 33 Elbadawi et al found that M‐TEER was increasingly performed in both White and Black patients at similar rates.…”
Section: Discussionmentioning
confidence: 67%
“…While different in scope from our study, studies that focus exclusively on transcatheter interventions, both edge‐to‐edge repair and replacement, have shown equivalent or improved outcomes for women compared with men. 23 , 24 , 25 The reasons underlying this difference between surgical and transcatheter outcomes between men and women are unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 99%